2013
DOI: 10.1002/jgrd.50780
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ocean feedback on tropical cyclone energetics under idealized air‐sea interaction conditions

Abstract: [1] The effects of ocean feedback on the energetic characteristics of the tropical cyclone (TC) are investigated based on idealized TC-ocean coupling simulations. Results reveal notable impacts of ocean response on TC energetics. The ocean feedback reduces the latent energy of TCs, and consequently less latent heat is released in TC clouds, which leads to an evident decrease of the kinetic energy. A bulk equivalent potential temperature (θ e ) budget analysis demonstrates that the upward heat fluxes at the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…As seen in Figure 7b, a considerable part of MSE extracted from the ocean has been transported from the boundary layer into the troposphere to fuel the TC engine. The peak values of upward propagation occur outside the eyewall, similar to the θ e budget in Ma et al [12]. Of interest is that the upward fluxes at the top of the boundary layer overtake the surface fluxes in the cold pool of MSE, which could lead to a decreased boundary-layer MSE in that region, as shown in Figure 7a.…”
Section: Column Mse Budgetsupporting
confidence: 69%
See 2 more Smart Citations
“…As seen in Figure 7b, a considerable part of MSE extracted from the ocean has been transported from the boundary layer into the troposphere to fuel the TC engine. The peak values of upward propagation occur outside the eyewall, similar to the θ e budget in Ma et al [12]. Of interest is that the upward fluxes at the top of the boundary layer overtake the surface fluxes in the cold pool of MSE, which could lead to a decreased boundary-layer MSE in that region, as shown in Figure 7a.…”
Section: Column Mse Budgetsupporting
confidence: 69%
“…outside the eyewall, similar to the θe budget in Ma et al [12]. Of interest is that the upward fluxes at the top of the boundary layer overtake the surface fluxes in the cold pool of MSE, which could lead to a decreased boundary-layer MSE in that region, as shown in Figure 7a.…”
Section: Column Mse Budgetsupporting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, Reference [41] discussed the role of latent and sensible heat fluxes in the instability of the boundary layer, in which enhanced fluxes lead to instability and contribute to vigorous convection. Other authors [42,43] emphasized that the tropical cyclones extract latent energy from the ocean through latent heating and release it into the atmosphere through the convective clouds. Thus, a part of the latent heat released acts to increase the kinetic energy of the system.…”
Section: Synoptic Analysismentioning
confidence: 99%
“…A majority of Typhoon-Ocean interaction studies focused on the processes how the atmosphere acts on ocean. However, previous investigations showed that TCs-induced sea surface temperature (SST) cooling could feedback on their intensity (Lloyd and Vecchi, 2011;Vincent et al, 2012;Ma et al, 2013). Emanuel (1999) argued that the air-sea enthalpy difference decides the intensity of a TC.…”
Section: Introductionmentioning
confidence: 99%